Development of hand gesture classification system based on electromyography signals - A. A. Kabanov (Омский научный вестник)
The paper presents the results of research of electromyography signals and their application to control prostheses. There are compiled upper limb prostheses classification scheme. Signals are determined with the potential to identify them in various patterns responsible for the hand gestures. A program for processing signals has been developed to obtain the resulting patterns of hand movements in the LabView software environment. The main result of the program is the identification of possible gestures and the development of an appropriate response to control the prosthesis.